2013
DOI: 10.1007/s11145-013-9480-1
|View full text |Cite
|
Sign up to set email alerts
|

Writing fluency and quality in kindergarten and first grade: the role of attention, reading, transcription, and oral language

Abstract: In the present study, we examined the influence of kindergarten component skills on writing outcomes, both concurrently and longitudinally to first grade. Using data from 265 students, we investigated a model of writing development including attention regulation along with students’ reading, spelling, handwriting fluency, and oral language component skills. Results from structural equation modeling demonstrated that a model including attention was better fitting than a model with only language and literacy fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
99
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 48 publications
(109 reference statements)
14
99
2
8
Order By: Relevance
“…Attention was another cognitive skill that was hypothesized to be important for writing (Berninger & Winn, 2006), and it was related to writing quality and CBM writing in the present study, confirming previous findings in first grade and in kindergarten (Kent et al, 2014; Kim et al, 2013). Interestingly, once children’s gender was accounted for, attentiveness was not related to writing quality although its relation remained for the CBM writing outcome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Attention was another cognitive skill that was hypothesized to be important for writing (Berninger & Winn, 2006), and it was related to writing quality and CBM writing in the present study, confirming previous findings in first grade and in kindergarten (Kent et al, 2014; Kim et al, 2013). Interestingly, once children’s gender was accounted for, attentiveness was not related to writing quality although its relation remained for the CBM writing outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Attention, in particular, has been shown to be related to writing for children in first and second grade (Hooper et al, 2002, 2011; Kent et al, 2014; Kim et al, 2014). Additional evidence underscoring the importance of attention in writing comes from studies with children who have Attention Deficits or Attention Deficit Hyperactivity Disorder (ADHD); converging evidence suggests that students with ADHD made more spelling and grammatical errors (Casas, Ferrer, & Fortea, 2013; Gregg, Coleman, Stennett, & Davis, 2002; Re, Pedron, & Cornoldi, 2007), made more content errors or digressions, and demonstrated weaker text structure features than children without ADHD (Casas et al, 2013).…”
Section: Predictors Of Writing Skillsmentioning
confidence: 99%
“…We found that word reading and spelling were both highly related in kindergarten, which is convergent with previous studies with beginning readers and spellers (Ahmed et al, 2014; Kim, 2011; Kent et al, 2014 a ; Byrne & Fielding- Barnsley, 1993; Ehri, 2000; Juel et al, 1986). As transcription skills are necessary and release cognitive resources for high-order processes, its impact on both writing quality has been hypothesized in developmental models of writing (e.g., Berninger & Winn, 2006; Juel et al, 1986).…”
Section: Discussionsupporting
confidence: 91%
“…However, it should be noted that the writing outcome in Hooper’s study was not written composition, but was composed of letter writing automaticity, writing fluency (i.e., writing words related to a topic), and sentence combining tasks. In our previous study, we found that children attention using a teacher-rated SWAN measure was concurrently related to writing for children in grade 1 (Kent et al, 2014). Furthermore, children’s attention in kindergarten has been shown to be predictive of their writing in grade 1 (Kim et al, 2014 b ).…”
Section: Attention and Writingmentioning
confidence: 94%
“…Anytime a student stopped writing he or she was prompted once to continue. Brief 5-minute writing tasks have been used extensively in prior writing research (Berninger et al, 1996;Connelly, Dockrell, Walter, & Critten, 2012;Graham et al, 1997;Kent, Wanzek, Petscher, Al Otaiba, & Kim, 2014), including curriculum-based measurement research (Espin et al, 2000), with proven validity (Dockrell, Connelly, Walter, & Critten, 2015;Lembke, Deno, & Hall, 2003). To control for potential prompt effects, half of the classes wrote the essay without planning to the prompt "Do you think teachers should give students homework every days?"…”
Section: Methodsmentioning
confidence: 99%